AutoML accurately predicts endovascular mechanical thrombectomy in acute large vessel ischemic stroke - Raj, Rishi; Kannath, Santhosh Kumar; Mathew, Jimson; Sylaja, P. N. (Frontiers in Neurology, 2023)
Background and Objective: Automated machine learning or autoML is widely been deployed in various industries. However, their adoption in healthcare, specially in clinical settings is constrained due to lack of clear understanding and explainability. The aim of this study is to utilize autoML for prediction of functional outcome in patients who underwent mechanical thrombectomy and compare it with traditional ML models with focus on explainability of the trained models.Methods: A total of 156 patients of acute ischemic stroke with Large Vessel Occlusion (LVO) who underwent mechanical thrombectomy within 24 hours of stroke onset were included in the study.A total of 34 treatment variables including clinical, demographic, imaging, procedure related data were extracted. Various conventional machine learning models such as decision tree classifier, logistic regression, random forest, kNN and SVM as well as various autoML models such as AutoGluon, MLJAR, Auto-Sklearn, TPOT and H2O were used to predict the modified Rankin score (mRS) at the time of patient discharge and at 3 months follow up. The sensitivity, specificity, accuracy and AUC for traditional ML and autoML models were compared.The autoML models outperformed the traditional ML models. For prediction of mRS at discharge, the highest testing accuracy obtained by traditional ML models for decision tree classifier was 74.11% whereas for autoML it was obtained through AutoGluon which showed an accuracy of 88.23%. Similarly, for mRS at 3 months, the highest testing accuracy of traditional ML was that of SVM classifier at 76.5% whereas that of autoML was 85.18% obtained through MLJAR. The 24 hour ASPECTS score was the most important predictor for mRS at discharge whereas for prediction of mRS at 3 months, the most important factor was mRS at discharge.Automated machine learning models based on multiple treatment variables can predict the functional outcome in patients more accurately than traditional ML models. The ease of clinical coding and deployment can assist clinicians in critical decision-making process. We have developed a demo application which can be accessed at https://mrs-score-calculator. onrender.com/ 1 Raj et al.